Family Roles and Support in Preventing Stunting: A Systematic Review - Nur Alam Fajar; Mohammad Zulkarnain; Ridha Taqwa; Kiki Sulaningsi; Esti Sri Ananingsih; Riris Diana Rachmayanti; Siau Ching Sin (Jurnal Promosi Kesehatan Indonesia, 2024)
Background: Stunting is inadequacy in physical growth. Stunting can be detrimental to children under five as it causes low intelligence, decreased endurance, and inhibited growth and development. This will increase risk of infections and non-communicable diseases in adulthood. The optimal implementation of family roles supports the improvement of nutritional status in toddlers so it can reduce the incidence of stunting.Method: This systematic review is written in accordance to the PRISMA guidelines. The process includes analysis on online articles from databases of ScienceDirect, PubMed, and Google Scholar for the past five years the period from 2019 with the keywords "stunting and parents or family".Results: There are researches from eight articles related to the role and support of families in preventing stunting. Based on several syntheses reviewed, it was determined that culture can be an inhibiting factor in preventing stunting. Still, with local wisdom, it can also be a catalyst in reducing stunting itself. Culture is one of the specific nutrition interventions that can reduce the prevalence of stunting by emphasizing aspects of a mother as the “center of life”, family roles and support, and the role of fathers in preventing stunting. Families have an important role to play in preventing and managing the problem of stunting. Families play an important role in preventing stunting at every stage of life from fetus in the womb, to newborn, toddler, teenager, married, pregnant, and so on. Therefore, efforts to empower families are necessary.